Rapid identification of microorganisms from platelet concentrates by matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry after short‐term incubation on liquid medium. Issue 3 (28th November 2017) - Chetouane, Yasmine; Dubourg, Gregory; Gallian, Pierre; Flaudrops, Christophe; Chiaroni, Jacques; Chabrière, Eric; Raoult, Didier; Camoin‐Jau, Laurence
Abstract : BACKGROUND: Platelets (PLTs) are especially affected by the risk of bacterial contamination. Matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) is an accurate method for the routine identification of bacterial isolates in microbiology laboratories. We directly applied the MALDI‐TOF method to bacterial detection in PLTs. In this study, we evaluated the sensitivity, specificity, and speed of a direct MALDI‐TOF approach compared to the conventional method BACTEC. STUDY DESIGN AND METHODS: Eight bacteria associated with PLT contamination, cited by the ISBT on transfusion‐transmitted infectious diseases, were spiked into PLTs for a final concentration of approximately 100 CFU/bag (n = 5 for each strain). The PLTs were then agitated for 24 hours. One milliliter of PLTs was incubated in a shaker incubator for 8 hours at 37°C with 1 mL of trypticase soy broth (TSB). The spectra were analyzed using the MALDI Biotyper software. As a control, 8 mL of PLTs incubated into BACTEC bottles and a positive bottle were subcultured to ensure identification of bacterial growth. RESULTS: Regardless of the strain of PLTs tested, MALDI‐TOF analysis made detection and early identification possible at 8 hours. Analysis by BACTEC of PLTs infected with Escherichia coli, Bacillus cereus, and Providencia stuartii made early identification possible. For the remaining bacteria, the detection time by BACTEC was significantly longer than 8 hours. CONCLUSION: We demonstrated the possibility of detecting bacteria in PLTs using a standardized culture step in TSB with MALDI‐TOF, regardless of the strain, with the same specificity and analytical sensitivity and with a time to results of 12 hours. This direct method presented rapid and reliable results.